Identification of Immune-Related lncRNA Prognostic Signature and Molecular Subtypes for Glioblastoma - Yu, Wanli; Ma, Yanan; Hou, Wenbin; Wang, Fang; Cheng, Wan; Qiu, Feng; Wu, Pengfei; Zhang, Guohua (Frontiers in Immunology, 2021)
Abstract Background Glioblastoma multiforme (GBM) is extensively genetically and transcriptionally heterogeneous, which poses challenges for classification and management. Long noncoding RNAs (lncRNAs) play a critical role in the development and progression of GBM, especially in tumor associated immune processes. Methods Immune-related lncRNAs (irlncRNAs) were screened, univariate and multivariate Cox regression analyses were utilized to construct a prognostic model. GBM specific CeRNA and PPI network was constructed to predict lncRNAs targets and evaluate the interactions of immune mRNAs translated proteins. GO and KEGG pathway analyses were used to show the biological functions and pathways of CeRNA network-related immunity genes (IGs). Consensus Cluster Plus analysis was used for GBM gene clustering. Then, we evaluated GBM subtype-specific prognostic values, clinical characteristics, genes and pathways, immune infiltration access single cell RNA-seq data, and chemotherapeutics efficacy. The hub genes were finally validated. Results 17 prognostically related irlncRNAs (PRirlncRNAs) were screened to build a prognostic model signature based 6 key irlncRNAs (H19, ST3GAL6-AS1, AL162231.2, SOX21-AS1, AC006213.5, and AC002456.1). Survival curve, risk Heatmap, risk curve, ROC curve, forest plots, and ROC plots was performed to conclude that the risk model indeed had a good predictive effect, and similar results in the validation set. Based on GBM specific CeRNAs and enrichment analysis, PLAU was predicted as a target of lncRNA-H19, and mainly enriched in the malignant related pathways. GS-A displayed the most favorable prognosis, high proportion of genes (IDH1, ATRX and EGFR) mutation, chemoradiotherapy and low risk, and characterized by low expression of four high-risk lncRNAs (H19, HOTAIRM1, AGAP2-AS1, and AC002456.1) and one mRNA KRT8. KRT8 may exert its biological activity through the T cell receptor, Apoptosis, or JAK/STATA signaling pathway. GBM subtypes (GSs) with poor survival were mainly infiltrated by mesenchymal stem cells (MSCs) and Astrocyte, and more sensitivity to gefitinib and roscovitine. Among GSs, three hub genes KRT8, NGFR and TCEA3 were screened and validated to potentially play feasible oncogenic roles in GBM. Conclusion Construction of lncRNAs risk model and identification of GBM subtypes under immune environment, suggesting the KRT8, NGFR, TCEA3 and irlncRNAs had the promising potential for clinical immunotherapy of GBM.